Development and validation of a questionnaire to determine knowledge, attitudes and practices in antibiotics prescription in dentistry - María del Pilar Angarita-Díaz; Diana Forero-Escobar; Julián Eduardo Mora-Reina; Lizeth Paola Torres-Gaona; Rossy Natalia Gómez-Trujillo (Universidad de Antioquia, 2019)
Introduction: antibiotic prescription in dentistry is usually performed during the treatment of oral infections or as a prophylactic measure for patients at risk; however, studies in other countries report an inadequate prescription by dentists. The purpose of this study was to validate a questionnaire to identify the knowledge, attitudes, and practices around antibiotic prescription by dentists. Methods: the study was developed in five stages: 1. A survey was designed. 2. Content validity by an expert panel. 3. A pilot study. 4. Application of the questionnaire to determine its unidimensionality, reliability, and psychometric index. 5. The scales were standardized to present the results independently of the number of questions. Results: in stages 1 and 2, a survey was developed showing an appropriate level of agreement by an expert panel (with the following Kendalle's W values: sufficiency: 0.68; consistency: 0.69; relevance: 0.72; clarity: 0.81). Stage 3 showed that the questionnaire was too long. In stage 4, some items did not satisfy psychometric indicators such as internal consistency. Therefore, the instrument was adjusted to 36 items, improving the psychometric index [biserial correlation coefficient > 0.0, discrimination index > = 0, non-response index between 0-0.15, unidimensionality (p = 0.93)] and obtaining good internal consistency (KR = 0.81). In stage 5, the questionnaire was qualified with a percentile rank in three levels: low, medium, and high. Conclusions: the results from this study indicate an appropriate and validated survey, with adequate number of items and scale scores. All this despite the fact that antibiotic prescription by dentists is complex due other factors that determine this process.